Methodology brut: Philosophy, Ecstatic Thinking, and Some Other (Unfinished) Things. (September 2015) - Koro-Ljungberg, Mirka; Carlson, David; Tesar, Marek; Anderson, Kate
A reminder: This text has been created as a series of brut and raw responses representing a collective of "impossible" imaginings. Our collective writing is not about the vision or about insights into the future of qualitative inquiry per se, but it is about ways in which some qualitative researchers wish to stay methodologically and theoretically in flux and motion. We desire to face this uncertainty, rawness, and creative chaos by engaging in collective thinking without constant and continuous purification and "cleaning" efforts. The future of qualitative inquiry is not one but multiple; thus, there cannot be one "vision" but all visions; visions on top of other visions, visions continuing other visions, visions contradicting others, visions lacking and desiring something that cannot be described, understood, or had.